Book review: Promoting healthy childhood development today. James R. Harris, Jr., Ph.D. Holyoke, MA., Neari Press, 2007. 92pp, ISBN: 1-929657-30-7 - George Hollowell (Scottish Journal of Residential Child Care)
Promoting healthy childhood development today, by James R. Harris, Jr., Ph.D., serves as a useful introduction to those working with children and young people in many different capacities, including parents, foster carers and residential child care practitioners, among others. The book tasks itself as a jargon free and practical guide for people working with young people. As the author explains in his introduction, 'the text aims to provide adults with information and strategies to help them address child-rearing issues' (p. XIV). It applies theory to practical examples in a meaningful way, helping people who work with or care for children to understand behaviour as part of a child's development.